2009
DOI: 10.1007/s10404-009-0521-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of viscosities of dispersed and continuous phases in microchannel oil-in-water emulsification

Abstract: Although many aspects of microchannel emulsification have been covered in literature, one major uncharted area is the effect of viscosity of both phases on droplet size in the stable droplet generation regime. It is expected that for droplet formation to take place, the inflow of the continuous phase should be sufficiently fast compared to the outflow of the liquid that is forming the droplet. The ratio of the viscosities was therefore varied by using a range of continuous and dispersed phases, both experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
66
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 19 publications
7
66
1
Order By: Relevance
“…4a) is an important parameter in determining droplet size (Kawakatsu et al 2001). Our previous study using the MC array (MS104) demonstrated that droplet size was not influenced by the viscosity ratio above a critical value of 4 (van Dijke et al 2010). The viscosity of both phases was varied in this case.…”
Section: Temperature Dependence Of Droplet Generation By MC Emulsificmentioning
confidence: 87%
See 2 more Smart Citations
“…4a) is an important parameter in determining droplet size (Kawakatsu et al 2001). Our previous study using the MC array (MS104) demonstrated that droplet size was not influenced by the viscosity ratio above a critical value of 4 (van Dijke et al 2010). The viscosity of both phases was varied in this case.…”
Section: Temperature Dependence Of Droplet Generation By MC Emulsificmentioning
confidence: 87%
“…The viscosity ratio, defined as the ratio of the viscosity of the dispersed phase to the viscosity of the continuous phase, also decreased exponentially by 2.7 times as temperature increased. The viscosity ratio values were in the range of 28-77 at T C of 10-70°C, which range is above 4 the critical viscosity ratio determined by van Dijke et al 2010, where droplet size is not influenced by viscosity ratio. The interfacial tension for the two-phase system containing SDS increased by 2.0 times as T C increased from 10 to 70°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Symmetric MCs are of the same size and shape (e.g., circular or rectangular) along the whole cross section of the plate. Rectangular MCs provide better performance in MCE than circular MCs and an aspect ratio of slot length to slot width should be at least 3−3.5 to ensure production of uniform droplets (Kobayashi et al 2004(Kobayashi et al , 2009avan Dijke et al, 2010c).…”
Section: Straight-through Microchannel Arraysmentioning
confidence: 99%
“…But long term stability of the nanofluids could be a practical issue. Long term stability of nanoparticle suspensions is critical to fully appreciate the benefits of nanofluids (Das et al 2008).…”
Section: Nanoal 2 O 3 Powdermentioning
confidence: 99%